Lūthāng kānphatthanā kānth̨ōngthīeo Čhangwat ʻUd̨ōn Thānī : rāingān chabap sombūn (Khrōngkān Sưksā Lūthāng Kānphatthanā Kānth̨ōngthieo Čhangwat Ud̨ōn Thānī ; Sūn B̨ōrikān Wichākān, Mahāwitthayālai Kh̨ōn K̄æn, 1996)
Study on tourism industry development projects in Udon Thani Province, Northeastern Thailand.